Climate resilient agriculture and enhancing food production: Field experience from Agusan del Norte, Caraga Region, Philippines - Varela, Rowena P.; Apdohan, Arnold G.; Balanay, Raquel M. (Frontiers in Sustainable Food Systems, 2022)
This paper describes the assessment of climate risks, the vulnerability of farmlands, and the adaptive farming practices to climate change with the use of GIS, field observations, stakeholder consultation and interviews and case documentation. GIS-based climate risk vulnerability assessment maps were generated to pinpoint the areas with the major climate hazards in Agusan del Norte. The vulnerability of the farmlands, and the adaptive capacity of the farms were assessed with index scoring. Also, adaptation to climate change based on the most problematic hazard (flooding) was observed on the two groups of farmers (with and without climate resilient agriculture (CRA)/cropping system adjustments) for cost and benefit comparison. The results show flooding and drought as the significant hazards in Agusan del Norte (Caraga Region) and high vulnerability to these hazards due to low coping mechanisms for most farms. Low adaptive capacity was also observed among these farms. Case-based observations on adaptation in Jabonga, Agusan del Norte revealed that well-timed adjustments to the usual cropping system can increase farm income despite of the flood and inundation for 2–3 months. This study recommends for harmonized measures toward advocating strengthened adaptive capacity for agriculture across Agusan del Norte. Further climate R&D and increasing policy support on climate financing and CRA options are highly encouraged for the agricultural stakeholders to take action. For hard-pressed farmers with constrained access to improved varieties and technologies, timing is potentially essential to circumvent damages from climate change to gain economic and psychosocial benefits with well-timed adaptation measures.